Pengaruh Budaya Organisasi terhadap Kinerja Karyawan PT Budiman Maju Megah Farmasi (Bumame) Bandung - Silmi Nadhira Setiawan; Puspita Wulansari (Jurnal Informatika Ekonomi Bisnis, 2023)
This study used a non-probability sampling technique on a sample of 125 workers at PT. Budiman Maju Megah Pharmacy to determine the effect of organizational culture on employee performance. Simple linear regression analysis is a data analysis method used to explain research findings. The findings show a good and substantial impact of organizational culture on worker performance at PT. Budiman Maju Megah Pharmacy. Because a positive and consistent business culture can improve staff morale and performance to give the best results. Utilizing the principles and values ​​that offer direction and guidance to achieve organizational goals, businesses can develop a positive and healthy corporate culture. This study is anticipated to serve as a resource for other research that investigates how organizational culture influences employee performance.